2020
DOI: 10.1371/journal.pone.0230535
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of femoral access-site and access-related vascular complications following percutaneous coronary interventions (PCI)

Abstract: Background Major vascular complications (VCs) of ilio-femoral arterial access after percutaneous coronary interventions are infrequent, but are associated with increased mortality and morbidity. Routine endovascular repair of VCs is becoming the treatment of choice, especially for patients who cannot tolerate vascular surgery due to advanced cardiovascular disease or are in a bailout situation. Here, we review the different types of vascular access site complications associated with percutaneous coronary inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…Other studies indicated even a higher complication rate of up to 17% [10]. A recent study performed by the University Hospital of Bonn, Germany, reports 1.9% of vascular complications following PCI [11]. Putting our data into perspective, the total PCP-related ASC-rate of 1.6% is lower than compared to the historical data, indicating a time-and experience-dependent decrease of ASC.…”
Section: Procedures Types and Complication Ratecontrasting
confidence: 44%
“…Other studies indicated even a higher complication rate of up to 17% [10]. A recent study performed by the University Hospital of Bonn, Germany, reports 1.9% of vascular complications following PCI [11]. Putting our data into perspective, the total PCP-related ASC-rate of 1.6% is lower than compared to the historical data, indicating a time-and experience-dependent decrease of ASC.…”
Section: Procedures Types and Complication Ratecontrasting
confidence: 44%
“…It also reduces the overall length of hospital stay. More importantly, this technique reduces exposure to the risks of general anesthesia in a group of patients who are often affected by advanced CVD [3]. In the above presented case, our patient had just undergone a complex high-risk PCI and given her age and overall comorbidities, the patient was deemed a high cardiac risk for surgery.…”
Section: Discussionmentioning
confidence: 92%
“…Percutaneous endovascular repair of VCs is quickly becoming the preferred therapeutic intervention, especially for patients who cannot tolerate vascular surgery due to advanced cardiovascular disease (CVD) [3]. Aortic bifemoral bypass is an established method of treatment of peripheral vascular disease such as iliac artery disease depending on the type of lesion [4,5].…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 10 Other management techniques for the loss of access and hemorrhagic event includes active pressure over the puncture site, placement of a covered stent, prolonged balloon angioplasty, and direct surgical cut-down of the vessel. 11 , 12 , 13 To the best of our knowledge, this alternative closure technique is only possible owing to the dual action of this specific closure device. The intravascular balloon prevents slipping of this device while limiting the hemorrhage; the sealant that is deployed in the outside of the vessel provides the needed agents for thrombosis.…”
Section: Discussionmentioning
confidence: 99%